Diffuse benign inflammatory gastric polyps: A rare case in a young female: Case report and review of the literature - Zhang, ZongYao; Guo, ZhengChang; Zhang, JiaJia; Yu, Xin (Frontiers in Surgery, 2023)
Background:gastric polyps (GP) are one of the most common clinical diseases arising from the mucosal surface of the stomach. The benign nature of the gastric polyp and its absence of symptoms has been widely accepted. While diffuse benign inflammatory polyps spanning the entire gastric mucosa are relatively rare in young people. Case presentation: Our objective was to report a 20-year-old woman presenting with epigastric pain and vomiting, Upper Gastrointestinal Barium Contrast Roentgenography demonstrated a huge defect in the filling of the stomach. Upper endoscopy also showed the presence of dense inflammatory polyps in the stomach that were the cause of the severe pylorus obstruction.The diffuse benign gastric polys were diagnosed as inflammatory gastric polys on the basis of findings on histopathological examination.She was delivered as a result of the operating procedure of total gastrectomy and Roux-en-Y anastomosis of the esophagus of jejunum. Postoperative nutritional support therapy was also implemented.Postoperative pathological examination revealed inflammatory papillary and villous polyps distributed over the stomach, and eosinophilic infiltration was found in the local area of the polyp. Polyps move like tufts of coral. During the sixteen month follow-up, patients with symptoms of malnutrition and anemia recovered. Conclusions: Nutritional support and total gastrectomy were used to improve this patient's symptoms of malnutrition and anemia. Surgical intervention with appropriate nutritional support should be actively performed in these patients, while strengthening the differential diagnosis of hereditary disease.